Heart rate variability and suicidal behavior. (30th June 2016) - Wilson, Scott T.; Chesin, Megan; Fertuck, Eric; Keilp, John; Brodsky, Beth; Mann, J. John; Sönmez, Cemile Ceren; Benjamin-Phillips, Christopher; Stanley, Barbara
Abstract: Identification of biological indicators of suicide risk is important given advantages of biomarker-based models. Decreased high frequency heart rate variability (HF HRV) may be a biomarker of suicide risk. The aim of this research was to determine whether HF HRV differs between suicide attempters and non-attempters. Using the Trier Social Stress Test (TSST), we compared HF HRV between females with and without a history of suicide attempt, all with a lifetime diagnosis of a mood disorder. To investigate a potential mechanism explaining association between HF HRV and suicide, we examined the association between self-reported anger and HF HRV. Results of an Area under the Curve (AUC) analysis showed attempters had a lower cumulative HF HRV during the TSST than non-attempters. In addition, while there was no difference in self-reported anger at baseline, the increase in anger was greater in attempters, and negatively associated with HF HRV. Results suggest that suicide attempters have a reduced capacity to regulate their response to stress, and that reduced capacity to regulate anger may be a mechanism through which decreased HF HRV can lead to an increase in suicide risk. Our results have implications for the prevention of suicidal behavior in at-risk populations. Highlights: We investigated the association between heart rate variability and stress response. We compared suicide attempters and non-attempters with a social stress paradigm. Suicide attempters had a lower cumulative HRV during the task than non-attempters. Increase in anger was greater in attempters, and negatively associated with HRV. Attempters showed a reduced capacity to regulate the physiological stress response.